Un Decenio de Observaciones Climáticas Para Valdivia (1907 - 1916) y su Proyección Ecológica - Montaldo B., Patricio (Bosque (Valdivia), 1982)
A paper about the climate, phenology and other observation taken in Valdivia by Ing. Ricardo Harnecker during 1907 - 1916 period is sintetized. These observations are compared with the actual knowledges and their ecological proyection is pointed out.